2008
DOI: 10.1128/jvi.01796-07
|View full text |Cite
|
Sign up to set email alerts
|

3′ RNA Elements in Hepatitis C Virus Replication: Kissing Partners and Long Poly(U)

Abstract: The hepatitis C virus (HCV) genomic RNA possesses conserved structural elements that are essential for its replication. The 3 nontranslated region (NTR) contains several of these elements: a variable region, the poly(U/UC) tract, and a highly conserved 3 X tail, consisting of stem-loop 1 (SL1), SL2, and SL3. Studies of drug-selected, cell culture-adapted subgenomic replicons have indicated that an RNA element within the NS5B coding region, 5BSL3.2, forms a functional kissing-loop tertiary structure with part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
159
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(166 citation statements)
references
References 54 publications
6
159
1
Order By: Relevance
“…3). It has been reported that the length and composition of the poly(U/UC) tract is important for the replication of HCV replicons (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). However, no replication advantage of a poly(U/UC) tract longer than 86 bp was revealed in this study.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…3). It has been reported that the length and composition of the poly(U/UC) tract is important for the replication of HCV replicons (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). However, no replication advantage of a poly(U/UC) tract longer than 86 bp was revealed in this study.…”
Section: Discussioncontrasting
confidence: 41%
“…Each segment of HCV was cloned into this vector to generate the full-length clones. The HCV-KT9 clone was established using the 39-terminal fragment with the longest poly(U/UC) tract length (115 nt), which should have a high replication ability (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). A clone with a shorter poly(U/UC) tract length (86 nt), HCV-KT1, was also generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5'ppp was necessary but not sufficient for stable binding of HCV PAMP RNA by RIG-I. In terms of the HCV genome, well-defined internal RNA interactions of the 5' and 3' ends 21,22 could provide 5'ppp and PAMP motif proximity for stable RIG-I binding. The poly-U/UC motif is an essential determinant of HCV replication fitness 21 .…”
mentioning
confidence: 96%
“…In terms of the HCV genome, well-defined internal RNA interactions of the 5' and 3' ends 21,22 could provide 5'ppp and PAMP motif proximity for stable RIG-I binding. The poly-U/UC motif is an essential determinant of HCV replication fitness 21 . Thus, while the virus must maintain this motif for its viability, the host takes advantage of this requirement and targets the poly-U/UC region as a discriminator of PAMP RNA through RIG-I interaction.…”
mentioning
confidence: 99%